Visit-to-Visit Variability of Blood Pressure Is Associated With Hospitalization and Mortality in an Unselected Adult Population. (31st May 2018) - Basson, Marc D; Klug, Marilyn G; Hostetter, Jeffrey E; Wynne, Joshua
Abstract: BACKGROUND: Blood pressure variability (BPV) has been associated with poor health outcomes in high-risk patients, but its association with more general populations is poorly understood. METHODS: We analyzed outcomes from 240, 622 otherwise unselected patients who had 10 or more outpatient blood pressure readings recorded over a 3-year period and were aged from 20 to 100 years. RESULTS: Whether calculated as SD, average change, or greatest change and systolic or diastolic blood pressure, we found that higher outpatient BPV was associated with subsequent hospitalization and mortality. Systolic pressure average change exceeding 10–12 mm Hg or diastolic exceeding 8 mm Hg significantly increased risk of hospitalization and death (odds ratios [ORs] from 2.0 to 4.5). Variability in the highest decile increased risks even more dramatically, with propensity-matched ORs from 4.4 to 42. A systolic change exceeding 35 mm Hg increased the relative risk of death 4.5-fold. Similarly, a diastolic change greater than 23–24 mm Hg almost tripled the risks of hospitalization and death. Neither stratification for hypertension nor propensity matching for risk factors within the database affected these associations. CONCLUSIONS: Systolic and diastolic variabilities were each associated with subsequent adverse outcomes. Physicians should pay special attention to patients with swings in blood pressure between clinic visits. Electronic medical records should flag such variability.